The complementizer phase subjects and operators - Panagiotidis, Phoevos (Oxford : Oxford University Press, 2010)
This text addresses the role complementisers and their phrases play in the phase-based approach to the mental computation of language. Leading linguists and promising young scholars draw on analyses of a wide range of languages to consider how complementisers behave in subject extraction phenomena.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Grammar, Comparative and general -- Complement